Assessment of Tongue Scraper and Using Baking Soda Mouth Wash in Reduction of Halitosis : Halitosis Reduction by Mouthwash - Talpur, Pirah; Rajpar, Shazia Parveen; Talpur, Nida; Memon, Khalida Naz; Unar, Javaid; Kandhro, Rehmatullah (Pakistan Journal of Health Sciences, 2024)
<span class="NormalTextRun SCXW220024841 BCX0" data-ccp-parastyle="Normal1" data-ccp-parastyle-defn=""ObjectId":"4c1602ff-3dcd-4669-bef5-03edd318b8fc|56","ClassId":1073872969,"Properties":[469775450,"Normal1",201340122,"2",134233614,"true",469778129,"Normal1",335572020,"1",469777841,"Times New Roman",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman",268442635,"26",335559704,"1025",335559705,"1033",335551547,"1033",335559685,"10",335559740,"268",201341983,"0",335559739,"163",335551550,"6",335551620,"6"]">Bad breath, also known as halitosis, is a symptom in which a noticeably unpleasant breath odor is present. It can result in anxiety among those affected. It is also associated with depression and symptoms of obsessive compulsive disorder. Objective: To compare the effectiveness of tongue scraper and sodium bicarbonate (baking soda) mouthwash in reduction of halitosis. Methods: This comparative cross-sectional study was organized in undergraduate students of Paramedics Liaquat University of Medical and Health Sciences (LUMHS), Jamshoro. Individuals aged 18 to 30 years of age were included by non-probability convenient sampling technique. Data were analysed by SPSS Version-26.0. Results: A total of 302 cases were comparatively studied. Males were in preponderance in both groups. Before treatment, 2.6% had slight odor, 33.8% had moderate odor, 28.5% had heavy odor, 23.85% had strong odor and 11.2% had intense odor in Group A, while 14.6% had slight odor, 19.9% had moderate odor, 25.8% had heavy odor, 21.8% had strong odor and 17.8% had intense odor in Group B (p=0.04). After treatment baking soda mouthwash showed more efficacious in terms of decrease the halitosis and its severity. In 21.2% halitosis was completely reduced and remaining most of the cases had mild and moderate halitosis compared to tongue scraper technique, while strong odor was completely reduced in both groups (p-0.001). Conclusions: Sodium bicarbonate (baking soda) mouthwash was observed to be the more effective in terms of decrease the halitosis and its severity compared to the tongue scraper technique among individuals presented with halitosis.